2014
DOI: 10.4049/jimmunol.1302258
|View full text |Cite
|
Sign up to set email alerts
|

Role of Th1/Th17 Balance Regulated by T-bet in a Mouse Model of Mycobacterium avium Complex Disease

Abstract: Th1 immune responses are thought to be important in protection against intracellular pathogens. T-bet is a critical regulator for Th1 cell differentiation and Th1 cytokine production. The aim of this study was to determine the role of T-bet in host defense against Mycobacterium avium complex (MAC) infection. Wild-type mice, T-bet–deficient mice, and T-bet–overexpressing mice were infected with MAC via intratracheal inoculation. Macrophages and dendritic cells obtained from these mice were incubated with MAC. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 49 publications
2
28
0
Order By: Relevance
“…A number of studies have demonstrated that MAC disease is associated with the host immune system [ 4 – 7 ]. A granuloma is a characteristic pathophysiological feature induced by mycobacterial infections, and is an important element of the host defense system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies have demonstrated that MAC disease is associated with the host immune system [ 4 – 7 ]. A granuloma is a characteristic pathophysiological feature induced by mycobacterial infections, and is an important element of the host defense system.…”
Section: Introductionmentioning
confidence: 99%
“…Th1 cells also play a central role in protection against intracellular pathogens and induce activation of macrophages. Thus, they are deeply involved in inflammation and granuloma formation, which play critical roles in protection against MAC [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The transcription factor T-box expressed in T cells (T-bet) is known as the critical regulator of Th1 differentiation and Th1 cytokine production [ 8 ]. We recently demonstrated that T-bet-overexpressing mice were resistant to pulmonary MAC infection and their cytokine expression was shifted toward Th1 phenotype [ 9 ]. However, T-bet-deficient mice were susceptible to MAC and had a higher expression of Th17 cytokines, such as IL-6 and IL-17.…”
Section: Introductionmentioning
confidence: 99%
“…Key observations made in T-bet-deficient mice were validated in this human patient with T-bet deficiency: 1) the development of TH1 cells and their production of effector cytokines, including IFN-g in particular, requires T-bet (Szabo et al, 2000(Szabo et al, , 2002; 2) the development of NK and iNKT cells is dependent on T-bet (Townsend et al, 2004) (Table S8); 3) the regulation of T-bet-dependent targets, including CXCR3, TNF and IFNG, involves both direct transactivation and epigenetic modulation (Miller and Weinmann, 2010). Accordingly, T-betdeficient mice are highly vulnerable to mycobacteria, including Mycobacterium tuberculosis and Mycobacterium avium (Matsuyama et al, 2014;Sullivan et al, 2005), like mice deficient for other genes that govern IFN-g immunity (Casanova, 1999). By contrast, despite the requirement of Tbet for immunity against a broad spectrum of pathogens following experimental inoculation in mice, the only apparent infectious phenotype of the T-bet-deficient patient is MSMD (Table S9).…”
Section: Discussionmentioning
confidence: 99%